Animal encyclopedia - Elphick, Jonathan (London : Dorling Kindersley, 2000)
Provides information about the physical characteristics, habits, and behavior of such animals as hedgehogs, peacocks, penguins, salamanders, and snakes.
Includes glossary and index
Primary
Keywords: Encyclopedia and dictionaries